2020
DOI: 10.1016/j.chest.2020.03.059
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Symptoms During the First Year Following ARDS

Abstract: BACKGROUND: Fatigue is commonly reported by ARDS survivors, but empirical data are scarce. RESEARCH QUESTION: This study evaluated fatigue prevalence and associated variables in a prospective study of ARDS survivors. STUDY DESIGN AND METHODS: This analysis is part of the ARDSNet Long-Term Outcomes Study (ALTOS) conducted at 38 US hospitals. Using age-and sex-adjusted, time-averaged random effects regression models, we evaluated associations between the validated Functional Assessment of Chronic Illness Therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
64
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 47 publications
7
64
1
1
Order By: Relevance
“…9 The mean transformed FACIT-F score AE SD that we found in the patients was 66 AE 12, which is quite similar to the 62 AE 18 found by Neufeld et al 8 This finding may be surprising considering that the patients we presented were less critically ill than those of Neufeld et al 8 (mean ICU length of stay, 10 AE 11 and 14 AE 11 days, respectively). Considering that the transformed FACIT-F score for the normal US population is 74.7 AE 15, 7 both studies 8,9 suggest that, generally, ICU survivors at 1 year suffer from symptoms of fatigue, especially younger patients with ARDS (mean age, 49 AE 15 years 8 and 68 AE 11 years, respectively). 9 Furthermore, the authors pointed out that the prevalence of fatigue at 6 months was greater than impaired physical function, impaired cognition, anxiety, or depression.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…9 The mean transformed FACIT-F score AE SD that we found in the patients was 66 AE 12, which is quite similar to the 62 AE 18 found by Neufeld et al 8 This finding may be surprising considering that the patients we presented were less critically ill than those of Neufeld et al 8 (mean ICU length of stay, 10 AE 11 and 14 AE 11 days, respectively). Considering that the transformed FACIT-F score for the normal US population is 74.7 AE 15, 7 both studies 8,9 suggest that, generally, ICU survivors at 1 year suffer from symptoms of fatigue, especially younger patients with ARDS (mean age, 49 AE 15 years 8 and 68 AE 11 years, respectively). 9 Furthermore, the authors pointed out that the prevalence of fatigue at 6 months was greater than impaired physical function, impaired cognition, anxiety, or depression.…”
supporting
confidence: 82%
“…In this field, the use of tools assessing patient-reported outcomes is widespread, and as far as fatigue is concerned, a dedicated tool to appraise the perceived fatigue in detail has been developed. 7 In this issue of CHEST, Neufeld et al 8 investigated the occurrence of fatigue assessed by the Functional Assessment of Chronic Illness Therapy (FACIT-F), after 6 and 12 months, in ARDS survivors. Interestingly, 70% and 66% of former patients with ARDS reported clinically significant symptoms of fatigue at 6 and 12 months, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The interplay of physical, cognitive and mental health impairments can lead to important functional problems, such as persistent fatigue, chronic pain and sleep dysfunction, and reduced health-related quality of life 8 . Moreover, globally, at 1-year follow-up, one-third of previously employed survivors of ICU stay are jobless 9 .…”
Section: Barriers To Meaningful Lifementioning
confidence: 99%
“…It has been found that cognitive impairment in ARDS survivors ranges from 70% to 100% at hospital discharge and 20% at 5 years, while mood deterioration including depression and post-traumatic stress disorder were also present [ 6 ]. Patients with COVID-19 seem to be prone to movement-related fatigue, similar to ARDS patients [ 7 ], even in those subjects not developing a critical illness. Therefore, the rehabilitation community is calling for action preparing for post-intensive care syndrome (PICS) in COVID-19 patients [ 8 – 10 ].…”
mentioning
confidence: 99%